2014
DOI: 10.1177/1457496914523412
|View full text |Cite
|
Sign up to set email alerts
|

Completeness and correctness of cholecystectomy data in a national register—gallriks

Abstract: Background and Aims: to validate the swedish register for gallstone surgery and endoscopic retrograde Cholangiopancreatography (gallriks) concerning completeness and correctness of entered data for cholecystectomies and evaluating the effect of repeated audits. it is crucial for any register to obtain a high accuracy in order to be a credible and reliable source for quality evaluation, research, and development.Materials and Methods: Completeness was determined by cross-matching the register with the swedish n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
59
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(59 citation statements)
references
References 17 publications
0
59
0
Order By: Relevance
“…19 In contrast to previous publications from tertiary referral centres, we report on an unselected population-based cohort of BDIs compared to a matched control group. This study presents a median follow-up interval of 4.3 years after cholecystectomy.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…19 In contrast to previous publications from tertiary referral centres, we report on an unselected population-based cohort of BDIs compared to a matched control group. This study presents a median follow-up interval of 4.3 years after cholecystectomy.…”
Section: Discussionmentioning
confidence: 98%
“…The register has been validated and 100% of BDIs were included in the register when compared with Löf, the national patient insurance register. 19 In Sweden approximately 12,000 cholecystectomies are performed annually and registered in GallRiks. 19,20 One third of cholecystectomies are performed as an emergency procedure, and laparoscopy is the dominating technique in both the planned (94%) and the emergency (82%) setting.…”
Section: Introductionmentioning
confidence: 99%
“…The coverage in regards to patients undergoing cholecystectomy is high in both GallRiks (82.9 %) and PAR (95.6 %). Furthermore, GallRiks has been validated with an overall correctness of registration in 97.2-98.2 % [23].…”
Section: Discussionmentioning
confidence: 99%
“…The register is continuously validated by independent observers in a blinded review of patient records at each participating hospital. Previous reviews have shown a high validity, with correct registrations and conformity with medical records in 97.9 % of all cases [13,23].…”
Section: Data Sourcesmentioning
confidence: 99%
“…The validation of GallRiks has demonstrated high correctness and completeness of data and no failure to report serious adverse events. 23 The registry attained an overall national coverage of approximately 90 % during the actual enrolment period.…”
Section: Methods Swedish Registry Of Gallstone Surgery and Endoscopicmentioning
confidence: 99%